SUSTAINABLE SUPPLY CHAIN IN THE DEVELOPMENT OF RENEWABLE ENERGY BASE ON BAMBOO FOREST BIOMASS (DEVELOPMENT SOLUTION FOR UNDERDEVELOPED AREAS IN INDONESIA) - JOHANNES W WAHONO; BAMBANG DWI WIJANARKO; UJANG SUMARWAN; BUSTANUL ARIFIN; HERRY PURNOMO (Management Department, Faculty of Economics and Business, Universitas Jambi, 2018)
The main objective of this study is to examine, with a comprehensive systematic approach and framework for the analysis of the economic feasibility and methodology of the application of bamboo forest biomass technology as renewable energy for the environment and sustainable regional development.This study was conducted in the subdistricts of South Siberut and Central Siberut, Mentawai Islands district, West Sumatra, as an example for the economic development of underdeveloped areas that have bamboo forests suitable for renewable energy materials.The result is a sustainanle supply chain of renewable energy development that addresses technical complexity, economic scale, capital costs, and renewable energy funding challenges, for small to medium-sized projects and not connected to off-grid networks